Detection of vertical deformation in Jakarta-Bandung high speed train route using X SAR and Sentinel - Julzarika, Atriyon; Rokhmana, Catur Aries (Geodesy and Cartography, 2019)
The Jakarta-Bandung high speed train is one of the national strategic plans. The high speed train route connects the Jakarta city to the Bandung city. The route needs to be detailed topography and checking of vertical deformations that occur along its route. This study aims to determine the conditions of vertical deformation in four stations and the Jakarta Bandung high speed train route. The spatial information of vertical deformation was extracted from the X SAR (2000) and Sentinel data (2018). The method used was Differential Interferometry Synthetic Aperture Radar (DinSAR). The vertical deformation was obtained from the reduction of topography in 2018 with the topography of 2000. Both of these topography must meet the tolerance of 1.96 sigma so that the resulting deformation is also more optimal. The results of this study can be used to reference the determination of high speed train route based on conditions of vertical deformation.